Scientific achievements of special pedagogy in the context of contemporary research challenges - Beata Cytowska (Studia z Teorii Wychowania)
The article presents the scientific and research achievements of special education, with particular emphasis on the last 10 years. In the introduction, the author presents the achievements of Maria Grzegorzewska, recognized as the founder of Polish special pedagogy, and then outlines the most important research achievements of scientists - special educators from the turn of the 20th and 21st centuries. Against this background, a review of the literature was presented using one of its forms, namely the study of the scope of literature. 73 monographs developed on the basis of research conducted by the author / author, in which the title, introduction and / or table of contents searched for "special education", "disability / person with disability" and "analysis of research results". The review includes subject(s), object(s) and research approach identified in the found literature. The obtained data were referred to research and development areas outlined by Amadeusz Krause in the article entitled Theoretical and empirical problems of special pedagogy. An outline of the research areas, published in the magazine "Disability. Scientific Half-Yearly " 2009 No. 1. This study was adopted as a reference because it was published 10 years ago, and the period 2009-2019 was designated to examine the contemporary achievements of special pedagogy in order to be able to determine the directions of development of the discipline, its most important achievements, dominant tendencies in the selection of research paradigms and outline development trends for the coming years.